Strategies and Challenges of Unified Payment Interface: Towards Facilitating a Digital Payments System in India - Kuriakose, Athul; Sajoy, P. B. (Journal of Telecommunications and the Digital Economy, 2023)
The Indian economy is gradually curtailing its overdependence on currency-based transactions and thereby moving closer to digital and mobile-based payment transactions. The main objective of the paper is to provide an in-depth theoretical understanding of the Unified Payments Interface (UPI), its current pace of growth and the possible future penetration based on polynomial trendline projection, the possible challenges that limit future penetration, and the various strategies to overcome these challenges. The paper used the previous six years’ UPI penetration statistics from 2016 to 2017 and established trends using polynomial trendline equation for the purpose of anticipating future penetration. The study also used statistics from published reports of the Reserve Bank of India (RBI) and the National Payment Corporation of India (NPCI) to draw meaningful conclusions on future UPI penetration. The study finds that the targeted one billion UPI transactions per day is achievable. The article contributes towards applied research by providing a decision-making tool to support policymakers, the government, and payment service providers, among others. Strategic applications of this research outcome include Unified Dispute and Issue Resolution processes, the RBI’s lapse management, customer protection measures, UPI limit management, expansion of  Internet user base and promoting digital financial inclusion in India.